5-level Cascaded H-Bridge Multilevel microgrid Inverter applicable to multiple DG resources with power quality enhancement capability - Mortezaei, Ali; Simoes, M. Godoy; Marafao, Fernando P. [UNESP]; Al Durra, Ahmed (Institute of Electrical and Electronics Engineers (IEEE), 2015)
This paper presents a 5-level Cascaded H-Bridge Multilevel Inverter (CHMI) able to perform several tasks and applicable to a microgrid with multiple local power sources. The current control strategy is based on the conservative power theory (CPT) generating references for different modes of operation. The primary merits of multilevel cascade voltage source inverters are the possibility of having independent DC sources, such as fuel cells, solar cells and batteries and, the reduced dc link voltage compare to the traditional 2-level inverters. Hence, the voltage stresses and switching losses are also decrease. In addition to injecting the available energy from DC sources into the grid, the CHMI has also being used to compensate voltage and current disturbances and to improve the power quality at point of common coupling. Additionally, the paper presents the analysis and design of cascaded voltage control scheme based on capacitor filter current feedback to regulate load voltage in islanded operation mode. The principles supporting the proposed control strategy are presented and the inverter performance is demonstrated through digital simulations using PSIM.
Keywords: Conservative Power Theory; Distributed Generation; Microgrid; Multilevel inverter; Power Quality Improvement